Magnitude, timing, and rate of slip along the Atacama fault system, northern Chile: implications for Early Cretaceous slip partitioning and plate convergence. Issue 3 (May 2021) - Seymour, N.M.; Singleton, J.S.; Gomila, R.; Mavor, S.P.; Heuser, G.; Arancibia, G.; Williams, S.; Stockli, D.F.
No abstract available